DEVELOPMENT OF BIOMAGZ BASED ON LOCAL WISDOM ON BIODIVERSITY MATERIAL IN HIGH SCHOOL - Wahyuningsih, Rina; Sukaesih, Sri; Peniati, Endah (Journal of Biology Education, 2019)
This study aims to describe the types of learning resources used previously at SMA N 3 Salatiga, describe the feasibility of Biomagz Based on Local Wisdom, and test the effectiveness of Biomagz Based on Local Wisdom on learning outcomes and student?s environmental care attitude. The method used is research development (R & D). Products are validated by material and media validators, and revised before being tested. Small-scale trials (readability test) use 10 students from class X MIPA 1, while large-scale trials use class X MIPA 2 with the experimental design Pre-experimental Design with the type of Pre-test and Post-test One Group Design. The results of the study show the variety of learning resources used previously including biological, teacher, internet, biology books, and the environment around students. The Feasibility of Biomagz Based on Local Wisdom obtained an average score of 92.21% with very decent criteria. Large-scale trials with an average N-gain value 0.49 in the medium category, the average classical completeness is 85.29%, and the environment care attitude of students is based on the observation result of 92.9% with a high category and the result of the inter-student assessment is 86, 18% with a high category. Based on the results of this study, it can be concluded that Biomagz Based Local Wisdom is well worth and effective on learning outcomes and student?s environmental care attitude.